Numerical solution for solving fuzzy volterra integral 2nd –kind by using modified decomposition technique - Jazzaa, Dakhaa Fadil; Abdulqader, Alan Jalal (Journal of interdisciplinary mathematics, 2023)
We discuss methods for solving the second-class fuzzy nonlinear Volterra -integral formula using novel error analysis and convergence techniques. The modified decomposition method is utilized to investigate convergence in the solution of the second class of fuzzy nonlinear Volterra integral formula. Moreover, some numerical examples were solved using our fuzzy equation. The presented methods were discussed in detail, and we compared the existing methods through the illustrative example that has been presented and applied creation classes to all the programming in Maple version (22). The quantity demand and investment in research and development, while the other model focuses on a more realistic relationship between the quantity demand and the price.